Pendidikan Kristen dari Orang Tua Berbasis Kesetaraan Gender bagi Remaja Suku Kayubatu - agnes thilova makanuay; Iky Sumarthina Prayitno (Voice of Wesley: Jurnal Ilmiah Musik dan Agama, 2021)
This article is an attempt to include Christian religious education as a form of gender equality learning for adolescents in the Kayubatu tribe. The Kayubatu tribe is one of the original tribes of Jayapura City, Papua Province. The Kayubatu tribe lives with a culture that has been preserved from generation to generation, one of which is an understanding of the Patriarchal culture. This understanding makes the people of the Kayubatu tribe live in gender inequality. Religion coexists with adat. Therefore, customs affect the whole system of life from generation to generation. Christian teaching patterns were first taught in family life and became very important to instill values Christian education in the form of equality for men and women. The author will discuss the views of women in customs and forms of Christian teaching that can be used as a form of gender equality for adolescents in Kayubatu village. During adolescence, children are considered capable of considering and having the will and awareness to act and be responsible, so gender equality education is expected to build awareness of adolescents so that they can practice equality between men and women in their environment. This research is a qualitative ethnographic research on the Kayubatu Village Community. Qualitative research is research that is used to investigate, discover, describe, and explain the quality or features of social influences that cannot be explained, measured or described through a quantitative approach.Keywords : Gender equality ; Christian education ; teneger